INVENTARISASI BEBERAPA MIKROORGANISME TERBAWA BENIH PADI YANG BERASAL DARI TALANG PADANG, KABUPATEN TANGGAMUS, LAMPUNG - Muhammad Nurdin . (Universitas Lampung, 2003)
Inventory of seed-borne microorganisms on paddy from District of Talang Padang, Tanggamus Lampung. This study was conducted to inventory microorganisms that infected or contaminated paddy seeds from District of Talang Padang, Lampung. Paddy seed samples were obtained by stratified random sampling method. Six villages were chosen from 28 villages, with six farmers from each village. From each farmer were collected 30 gram paddy seeds. Seventy grams seeds used as the work sample in seed health testing were obtained from 1080 gram of the composite sample. Testing method that been used were blotter test and agar test, then followed by growing-on test. Bacteria and seven genera of fungi were found to be associated with paddy seeds from this study. They were Alternaria, Fusarium. Aspergillus, Curvularia, Mucor, Rhizopus and Penicillium. Virus was not obtained in this study.